The general form of a polynomial is: x² + bx + c = 0. Substituting the roots,
3² + b(3) + c = 0
3b + c = -9 --> eqn 1
(5 + √5)² + (5 +√5)(b) + c = 0
(5+√5)b + c = -30-10√5 --> eqn 2
Solving both equations simultaneously by subtracting eqn 2 from eqn 1,
(-2 - √5)b = 21 + 10√5
b = -8 - √5
Using eqn 1,
3(-8 - √5) + c = -9
-24 - 3√5 + c = -9
c = -9 + 24 + 3√5
c = 15 + 3√5
Hence, the polynomial is: <em>f(x) = x² + (-8 - √5)x + (15 + 3√5)</em>.
Answer:
Length: 13.9 inches
Step-by-step explanation:
a^2 + b^2 = c^2
a = 8 and c= 16
8^2 + b^2 = 16^2
64 + b^2 = 256
b^2 = 256 - 64
b = sqrt 192
b = 13.9
Answer:
(3x5 - 10) • (10x5 + 3)
Step-by-step explanation:
Answer:
Step-by-step explanation:
Hello
Each large rectangle below represents one whole. What percent is represented by the shaded area?
9/10 = (9 x 10)/(10 x 10) = 90/100 = 90%